Improving Livestock Health Through the Implementation of Prevention and Treatment of Foot and Mouth Diseases - Pawestri, Wari; Riyanto, Joko; Yanti, Yuli; Wati, Ari Kusuma; Cahyadi, Muhammad (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Community service activities aim to transfer knowledge and technology related to the prevention and treatment of foot-and-mouth disease. The activity was carried out on June 22, 2025, at the Gemah Ripah livestock group, Jatikuwung, Gondangrejo, Karanganyar. The method used in the community service activities was Participatory Action Research (PAR). The community service began with an initial visit to the livestock group to identify the problems farmers faced. The activity continued with a group discussion on foot-and-mouth disease and its prevention and treatment. The following agenda item was to practice with a chopper machine and implement biosecurity using an electric tank. Monitoring and evaluation were conducted to monitor livestock health after the program. The results of the community service activity showed that 81.75% of livestock group members were of productive age, the majority of farmers were junior high/high school graduates, and they had an average of 6-10 years of livestock experience. The morbidity of foot and mouth disease reached 88.9% with a mortality rate of up to 5.5%. Implementation of biosecurity in livestock groups is still low (18.75%), and vaccination has been carried out by 43.75% of livestock breeders. 83.3% of farmers handled sick livestock themselves. Through group discussions and practical activities, farmers' knowledge increased by 60.6%. The conclusion is that this community service activity improved farmers' knowledge, which can serve as a basis for disease prevention and management.